Association of secondhand smoke exposure with cardiometabolic health in never-smoking adult cancer survivors: a population-based cross-sectional study - Kyuwoong Kim; Yoonjung Chang (BMC, 2022)
Abstract Background Little is known about the association of secondhand smoke (SHS) exposure with cardiometabolic health in adult cancer survivors, especially those who have never smoked. This study aimed to investigate the association of SHS exposure and cardiometabolic health in never-smoking adult cancer survivors. Methods Cross-sectional data of 830 adult cancer survivors aged more than 19 years who were never-smokers were identified from the Korea National Health and Nutrition Survey (KNHANES) 2013-2018, a nationally representative sample of the noninstitutionalized Korean population. SHS exposure was defined from self-reported survey and cardiometabolic outcomes (hypertension, general and abdominal obesity, hyperlipidemia, hypertriglyceridemia, reduced high-density lipoprotein, and impaired fasting glucose) were determined according to relevant criteria and data from the KNHANES. We used multiple logistic regression to compute odds ratio (OR) and 95% confidence intervals (95% CI) comparing those with and without SHS exposure for each outcome adjusted for potential confounders. Results Compared with the never-smoking adult cancer survivors without SHS exposure, those with SHS exposure had significantly higher odds for hypertriglyceridemia (OR = 1.63; 95% CI: 1.07-2.48). However, the other outcomes showed nonsignificant associations with SHS exposure (hypertension [OR = 1.33; 95% CI: 0.90-1.96]. general obesity [OR = 1.47; 95% CI: 1.47: 0.97-2.22], abdominal obesity [OR = 1.20; 95% CI: 0.82-1.75], hyperlipidemia [OR = 1.03; 95% CI: 0.68-1.55], reduced HDL-cholesterol [OR = 1.01; 95% CI: 0.70-1.45], and impaired fasting glucose [OR = 1.07; 95% CI: 0.72-1.58]. Conclusion This cross-sectional study suggests the association of SHS exposure with hypertriglyceridemia and provides evidence for marginal associations with other cardiometabolic risk factors in never-smoking adult cancer survivors. More studies are needed to develop evidence-based public health policies to minimize SHS exposure in adult cancer survivors.